Steroid-sparing effects and acceptability of a new skin gel containing the anti-inflammatory medicinal substance-nicotinamide - Djokic-Gallagher J; Rosher P; Hart V; Walker J (Dove Medical Press, 2019)
Jasmina Djokic-Gallagher, Phil Rosher, Valerie Hart, Jennine WalkerResearch and Development, Dermal Laboratories Ltd, Hitchin, SG4 7QR, UKBackground/aim: Adex gel (DENI) is a leave-on emollient, containing an ancillary anti-inflammatory medicinal substance, nicotinamide, for use in the treatment and management of dry skin conditions prone to inflammation. The aim of the study was to obtain patients’ and a Medical Investigator’s feedback on the clinical performance and acceptability of the product, and to assess the product’s potential for reducing patients’ reliance on topical corticosteroids and immunomodulators.Methods: Forty-eight patients were enrolled with 43 patients completing the study. These patients used the product on its own, or as adjunctive therapy, for two weeks instead of their usual emollient, applying it three times daily or more often if necessary. Using a questionnaire, subjects then indicated whether they were in agreement or not with various statements about the clinical performance and acceptability of the product. In the second part of the study, twenty patients used the product for four weeks, this time using it as often as they liked. The Medical Investigator looked at both the performance and the acceptability of the treatment. Patients completed a questionnaire again to indicate how they used it and whether their use of topical corticosteroids and/or immunomodulator treatments had changed.Results: Patient’s responses were very positive, ranging from 81% to 100% agreement with each performance statement in relation to beneficial effects on the skin. The Medical Investigator considered that for nearly all patients, DENI gel was a helpful and convenient addition to their treatment regime. When questioned on steroid-sparing effects, more than half reported that they needed to use less of their other anti-inflammatory treatments, and nearly 95% reported that they felt their skin condition had benefited from using DENI gel.Conclusion: This new anti-inflammatory emollient appears to be a helpful addition to the treatment armamentarium for eczema and psoriasis that may reduce reliance on topical corticosteroids and immunomodulators.Keywords: nicotinamide, emollient, steroid sparing effect, evidence